Dowry, Its Causes and Consequences: A Sociological Study of Dowry Harassment and Death Cases in Aligarh District of UP - Salim, Saira (International Journal of Scientific Research and Management (IJSRM), 2017)
Dowry refers to “the property, money, ornaments or any other form of wealth which a man or his familyreceives from his wife or her family at the time of marriage. Dowry is both a practice and a problem withIndian marriage” (Haveripeth, 2013).The practice of giving dowry was meant to assist a newly-wed coupleto start their life together with ease; however, now it has become a commercial transaction in whichmonetary considerations receive priority over the personal merits of the bride. Dowry system has given riseto many socio economic problems with very serious consequences. Numerous incidents of bride burning,harassment and physical torture of newlywed women and various kinds of pressure tactics being adopted bythe husbands/in-laws‟ pressurizing for more dowry have compelled the social reformers and theintelligentsia to give serious thoughts to various aspects associated with the institution of dowry (Sachdeva,1998).Government of India enacted “Dowry Prohibition Act” in 1961, which was further amended in 1985to control this menace. In spite of this Act, the “give and take” phenomenon of dowry is practiced widelythroughout India, irrespective of caste and class (Grantham, 2002). In many cases, when dowry amount isnot considered sufficient, the bride is often harassed, abused and tortured (Singh, 2005). Dowry relatedviolence and bride burning (dowry death) are only peculiar to our country and beside husband, his kin alsojoin together in persecuting the bride as the dowry and related customs provide a good excuse to them forhumiliating, insulting and even beating up of woman (Haveripeth, 2013)